Chemical enrichment of the ICM within the virgo cluster – I. Radial profiles. Issue 3 (10th February 2023) - Gatuzz, Efrain; Sanders, J S; Dennerl, K; Liu, A; Fabian, A C; Pinto, C; Eckert, D; Russell, H; Tamura, T; Walker, S A; ZuHone, J
ABSTRACT: We present a detailed analysis of the elemental abundances distribution of the Virgo cluster using XMM–Newton observations. We included in the analysis a new EPIC-pn energy scale calibration which allow us to measure velocities with uncertainties down to Δ v ∼150 km s −1 . We investigate the radial distribution of O, Ne, Mg, Si, Ar, S, Ca, Ni, and Fe. We found that the best-fitting model is close to a single-temperature component for distances >80 kpc and the cooler gas is more metal rich. Discontinuities in temperature are found around ∼30 and ∼90 kpc, which correspond to the radius of the cold fronts. We modelled elemental X/Fe ratio profiles with a linear combination of SNIa and SNcc models. We found a flat radial distribution of SNIa ratio over the total cluster enrichment, which supports an early ICM enrichment scenario, with most of the metals present being produced prior to clustering.